Performance Assessment of a Hybrid Solar-Geothermal Air Conditioning System for Residential Application: Energy, Exergy, and Sustainability Analysis - Yasser Abbasi; Ehsan Baniasadi; Hossein Ahmadikia (International Journal of Chemical Engineering)
This paper investigates the performance of a ground source heat pump that is coupled with a photovoltaic system to provide cooling and heating demands of a zero-energy residential building. Exergy and sustainability analyses have been conducted to evaluate the exergy destruction rate and SI of different compartments of the hybrid system. The effects of monthly thermal load variations on the performance of the hybrid system are investigated. The hybrid system consists of a vertical ground source heat exchanger, rooftop photovoltaic panels, and a heat pump cycle. Exergetic efficiency of the solar-geothermal heat pump system does not exceed 10 percent, and most exergy destruction takes place in photovoltaic panel, condenser, and evaporator. Although SI of PV system remains constant during a year, SI of GSHP varies depending on cooling and heating mode. The results also show that utilization of this hybrid system can reduce CO2 emissions by almost 70 tons per year.